2015
DOI: 10.1111/jch.12682
|View full text |Cite
|
Sign up to set email alerts
|

Improved Blood Pressure Control Using an Interactive Mobile Phone Support System

Abstract: This explorative, longitudinal study evaluated the effect of the daily use of a mobile phone‐based self‐management support system for hypertension in reducing blood pressure (BP) among 50 primary care patients with hypertension over 8 weeks. The self‐management system comprises modules for (1) self‐reports of BP, pulse, lifestyle, symptoms, and well‐being; (2) delivery of reminders and encouragements; and (3) graphical feedback of self‐reports. Daily use of the support system significantly reduced BP (systolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(99 citation statements)
references
References 49 publications
2
91
1
5
Order By: Relevance
“…The publication year of the studies ranged from 2012 to 2017 (see Table 1). Most studies (n=11) were conducted in the US [24][25][26][27][28][29][30][31][32] and Canada [33,34], while seven were carried out in European countries, including France [35], Sweden [36][37][38], Spain [39,40] and Italy [41]. The remaining three studies were conducted in China [42,43] and South Korea [44. Nine studies were randomised controlled trials (RCTs) [24,25,27,28,30,[33][34][35]42], ten were nonrandomised studies [26,29,31,32,37,[39][40][41]43,44], and two were qualitative studies [36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The publication year of the studies ranged from 2012 to 2017 (see Table 1). Most studies (n=11) were conducted in the US [24][25][26][27][28][29][30][31][32] and Canada [33,34], while seven were carried out in European countries, including France [35], Sweden [36][37][38], Spain [39,40] and Italy [41]. The remaining three studies were conducted in China [42,43] and South Korea [44. Nine studies were randomised controlled trials (RCTs) [24,25,27,28,30,[33][34][35]42], ten were nonrandomised studies [26,29,31,32,37,[39][40][41]43,44], and two were qualitative studies [36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Participants' average age ranged from 42.4 years [27] to 69.5 [42] years. The population groups of the studies included individuals with hypertension [24][25][26][27][28][29][30]32,[36][37][38][39][41][42][43][44], metabolic syndrome risk factors [34], and obstructive sleep apnoea with high cardiovascular risk [35], as well as overweight individuals [31]. Of the 21 included studies, 5 reported to have used behavioural theories, such as selfdetermination theory [24,26,27], motivational interviewing [30] and theory of planned behaviour [43] to underpin and guide the intervention methods and/or the development of the technology.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] Focussing on mHealth interventions in hypertension, a small study using a mobile-based self-management support system significantly reduced systolic (-7mmHg) and diastolic (-4.9 mmHg) BP over 8 weeks. [21] Further, a mobile phone based medication reminder application improved adherence and BP among patients with hypertension. [19] Thus, mHealth applications may serve to enhance hypertension control by providing a flexible, convenient platform for patient self-management.…”
Section: Introductionmentioning
confidence: 99%